IgG expressed by renal tubular epithelial cells in epithelial mesenchymal transformation and interstitial fibrosis in diabetic kidney disease - Xinyao Wang; Zhenling Deng; Yue Wang (Renal Failure)
Studies have reported that immunoglobulin G (IgG) "deposited" in the basement membrane of renal tubules is associated with tubulointerstitial damage in patients with diabetic kidney disease (DKD). Our previous study found that renal tubular epithelial cells (RTECs) can express and secrete IgG (RTEC-IgG) which may be associated with fibrosis. The present study aimed to explore the role of RTEC-IgG in renal tubulointerstitial fibrosis (TIF) in DKD. The results showed that RTEC-IgG expression was up-regulated in the renal tubulointerstitium of DKD patients and was associated with worse kidney function, more severe anemia, and higher interstitial fibrosis and tubular atrophy (IFTA) scores, and positively correlated with tubular epithelial mesenchymal transition (EMT) and TIF. IgG expression was also enhanced in the renal tubulointerstitium of DKD mice, which was positively correlated with TIF. High glucose induced an over expression of IgG in human renal tubular epithelial cells, and knockdown of IgG with siRNA relieved the expression of α-smooth muscle actin (SMA), collagen IV, fibronectin, and transforming growth factor (TGF)-β1 under high glucose conditions. In conclusion, our study suggests that RTEC-IgG is involved in the development of DKD by promoting EMT and interstitial fibrosis via TGF-β1.